Evolution and zoning of spatial ecosystem functional stability in the southern hilly region of China: a “structure–function” perspective - Li, Peijin; Liao, Yixin; Huang, Chen; Yi, Lang; Xie, Linglin (Frontiers in Ecology and Evolution, 2023)
Introduction A series of significant ecological construction projects in the southern hilly region have brought about substantial changes to the ecological status and comprehensive zoning of the region. Hunan Province, with its strategic significance, was chosen as a representative research subject in the southern hilly region. Methods We conducted a dynamic evaluation of the ecological status change and comprehensive zoning of Hunan Province from a structure–function perspective by applying the transfer matrix, Theil-Sen, Mann-Kendall, and ecosystem service trade-offs or synergies methods. The research goal was to integrate and harmonize structural complexity and functional diversification, providing valuable insights for optimizing both ecological background and territorial background. Results The main results are as follows: (1) The structural changes of ecosystems were mainly concentrated in settlement and Cropland ecosystems. While the area of bulti-up ecosystems has increased significantly, from 1.34% in 2000 to 2.72% in 2020. Cropland ecosystems marking a decrease of 1.39%, with a continued conversion of Cropland into construction land ecosystems. (2) Ecosystem function changes have introduced instability. Over time, NPP exhibited an oscillating trend of increase followed by a decrease. Spatially, there was a sharp decline in peripheral building land, and the regions of declining NPP displayed a lateral U-shaped distribution. (3) The overall trend in ecosystem service changes was positive. Quantitatively, GP and CS experienced an ascending-then-decreasing pattern, while HQ showed a weak decline and WY increased annually. At the county scale, there was noticeable spatial heterogeneity. Human socio-economic activities and environmental protection policies exert a significant impact on the ecological conditions within the study area. (4) Regarding the national territory space function partition, urban functional zones have primarily catered to residential functions and were mainly distributed in the Changsha-Zhuzhou-Xiangtan area. Discussion Ecological functional zones were mainly centered on ecological functions, and most were located in the mountainous areas of western and southern Hunan Province. The agricultural function areas were mainly to serve production functions and were mainly located in the Dongting Lake Plain, the nearshore plain of the mainstream and tributary systems of the rivers of Xiang, Zi, Yuan, and Li. In general, the changes in ecosystem structure and function in the study area reflect changes in ecological conditions. In the future, ecosystem diversity, stability, and sustainability should be improved from an integrated structure–function perspective.